IMPLEMENTASI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 30/PUU-XVI/2018 TERKAIT PELARANGAN JABATAN FUNGSIONARIS PARTAI POLITIK DALAM PENCALONAN ANGGOTA DPD - Bima Krisna Bayu; Rasji Rasji (Jurnal Hukum Adigama, 2021)
One of the problems in Indonesian constitutionality is the issue of implementation, several questions arose when the Constitutional Court decision Number 30 / PUU-XVI / 2018 was issued. In this decision, the Constitutional Court expanded the phrase "other work" as contained in Article 182 letter l of Law Number 7 of 2017 concerning General Elections. Then, this also becomes a problem when someone submits a judicial review of the general election commission regulations regarding the prohibition of political party functionaries from running as members of the Regional Representative Council. Regarding this, the Supreme Court Decision 65P / Hum / 2018 emerged, which in its decision contradicts the previously published and binding Constitutional Court Decision. The purpose of this research is to determine the implementation of the Constitutional Court Decision. The method used by the author is an approach method based on main raw materials, examining matters relating to principles, conceptions, doctrines, and the legal system by using secondary data. The result of the research conducted by the author is that the difference in these decisions creates legal uncertainty and contradicts the theory of erga omnes which requires legal awareness from various parties.